Acute toxicity of craniospinal irradiation with volumetric‐modulated arc therapy in children with solid tumors. Issue 7 (6th April 2018) - Wong, Kenneth K.; Ragab, Omar; Tran, Hung N.; Pham, Anthony; All, Sean; Waxer, Jonathan; Olch, Arthur J.
Abstract: Background: Craniospinal irradiation (CSI) is an important part of curative radiation therapy (RT) for many types of pediatric brain or solid tumors. After conventional CSI, long term survivors may experience sequelae due to unintended dose to normal tissue. Volumetric modulated arc therapy (VMAT) CSI reduces off‐target doses at the cost of greater complexity and error risk, and we describe our initial experience in a group of pediatric patients with solid tumors presenting with disseminated or recurrent disease. Procedure: Pediatric patients with brain tumors were identified at Children's Hospital Los Angeles from 2013 to 2015. Clinical characteristics, acute toxicity, and radiotherapy data were abstracted from their medical records. We identified 19 patients who received VMAT CSI. Quality assurance was performed with a cylindrical detector array and ion chamber measurements at the arc junctions. Results: Patients had medulloblastoma or supratentorial primitive neuro‐ectodermal tumor (n = 14, 11 high risk), germ cell tumors (two), relapsed neuroblastoma (two), and atypical teratoid/rhabdoid tumor (one). The most common acute toxicity was hematologic, including leukopenia (11% grade [Gr] 2, 26% Gr 3, and 63% Gr 4), anemia (89% Gr 2), and thrombocytopenia (16% Gr 1–2, 26% Gr 3, and 37% Gr 4). Despite leukopenia, we encountered only two Gr 3 infections (urinary tract and lung). The majority required blood products (89% red blood cells and 68% platelets). Weight loss was also common (47% Gr 1 and 26% Gr 2). Conclusions: VMAT CSI, along with chemotherapy and anesthesia, is feasible with supportive care. Daily image‐guided RT improves accuracy and reduces the risk of spinal cord overdose without increasing treatment time. Further research is needed to determine whether reducing doses to organs, such as thyroid, heart, or hippocampus, offsets the risk of increased volume of low‐dose irradiation.